2016
DOI: 10.7554/elife.16813
|View full text |Cite|
|
Sign up to set email alerts
|

A model for regulation by SynGAP-α1 of binding of synaptic proteins to PDZ-domain 'Slots' in the postsynaptic density

Abstract: SynGAP is a Ras/Rap GTPase-activating protein (GAP) that is a major constituent of postsynaptic densities (PSDs) from mammalian forebrain. Its α1 isoform binds to all three PDZ (PSD-95, Discs-large, ZO-1) domains of PSD-95, the principal PSD scaffold, and can occupy as many as 15% of these PDZ domains. We present evidence that synGAP-α1 regulates the composition of the PSD by restricting binding to the PDZ domains of PSD-95. We show that phosphorylation by Ca2+/calmodulin-dependent protein kinase II (CaMKII) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 72 publications
1
72
0
Order By: Relevance
“…Ras in turn promotes postsynaptic delivery of AMPARs (Zhu et al, ). Recent work now finds that CaMKII phosphorylation of SynGAP leads to displacement of SynGAP from the postsynaptic site, thereby fostering LTP (Araki et al, ; Walkup et al, ).…”
Section: Emerging Camkii Targets In Ltp: Syngap and Neuroligin‐1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ras in turn promotes postsynaptic delivery of AMPARs (Zhu et al, ). Recent work now finds that CaMKII phosphorylation of SynGAP leads to displacement of SynGAP from the postsynaptic site, thereby fostering LTP (Araki et al, ; Walkup et al, ).…”
Section: Emerging Camkii Targets In Ltp: Syngap and Neuroligin‐1mentioning
confidence: 99%
“…Ras in turn promotes postsynaptic delivery of AMPARs (Zhu et al, 2002). Recent work now finds that CaMKII phosphorylation of SynGAP leads to displacement of SynGAP from the postsynaptic site, thereby fostering LTP (Araki et al, 2015;Walkup et al, 2016). Finally, the postsynaptic cell adhesion protein neuroligin-1 is important for synapse formation by interacting with presynaptic neurexin (Scheiffele et al, 2000).…”
Section: Emerging Camkii Targets In Ltp: Syngap and Neuroligin-1mentioning
confidence: 99%
“…In a second biochemical study, we uncovered a function of synGAP unrelated to its GAP activity [37**]. We found that phosphorylation of synGAP by CaMKII at several sites progressively reduces the affinity of synGAP binding to all three PDZ domains of PSD-95.…”
Section: The Role Of Syngap In Induction Of Ltpmentioning
confidence: 99%
“…This result supports the hypothesis that synGAP acts as a placeholder by occupying PDZ domains “slots” on PSD-95. The effects of phosphorylation on affinity of synGAP for PDZ domains of PSD-95 further suggest that the placeholder function is regulated by activation of NMDARs [37]. …”
Section: The Role Of Syngap In Induction Of Ltpmentioning
confidence: 99%
“…synGAP, a dual Ras and Rap GTPase Activating Protein (GAP), is unusually highly concentrated in the PSD of excitatory synapses [2][3][4]. It binds tightly to the PDZ domains of PSD-95 [2,5] which serves to position it in close proximity to NMDA-type and AMPA-type glutamate receptors (NMDARs and AMPARs, respectively), and allows it to regulate the composition of the PSD by restricting binding of other proteins to PSD-95 [6].…”
Section: Introductionmentioning
confidence: 99%